FORMULATION OF HAIR GEL FROM CELERY ETHANOL EXTRACT (APIUM GRAVEOLENS .L) - Resva Meinisasti; Krisyanella Krisyanella; Dewi Oktasari (Proceeding B-ICON, 2022)
Background: Uncontrolled hair loss will cause baldness. Celery (Apium graveolens L.) contains compounds apiin, apigenin, mannitol, inositol, asparagine, glutamine, choline, linamarose potassium and sodium. Apigenin is the main chemical content in celery which is known to have activity as a vasodilator that can stimulate hair growth. The purpose of the study was to determine the hair gel formula that had the best characteristics. The concentration variations used were 5%, 7.5% and 10%. This study uses experimental research methods. The activity starts from the preparation of the ethanol extract of dried celery, gel formualtion, and then evaluation of the preparation. The evaluation of the preparations included organoleptic tests, homogeneity, spreadability, pH, irritation, freeze thraw and the preference of the preparations by the respondents. The results showed that Formulas 1 (5%) and 2 (7.5%) met the standard parameters of hair gel preparations, while formula 3 (10%) did not standardize the spreadability test. In the organoleptic test, it was seen that the higher the concentration of the extract used, the more concentrated the color of the preparation. However, the increase in extract concentration did not significantly affect the dispersion of the preparation. Based on the results obtained, it can be concluded that Formula 1 (5%) has the best hair gel preparation characteristics compared to other formulas.